Citrus greening disease investigation using micro synchrotron radiation X-ray fluorescence in association with soft independent modelling of class analogy (SIMCA) - Pereira, Fabiola Manhas Verbi [UNESP]; Milori, Debora Marcondes Bastos Pereira (My University, 2011)
This study describes the use of micro synchrotron radiation X-ray fluorescence (µSR-XRF) to investigate citrus greening disease in sweet orange (Citrus sinensis) plants. An experiment using healthy plants as control and plants of the same variety infected with Candidatus Liberibacter asiaticus (CLas) was performed to verify variations of the mineral composition of citrus leaves. A µSR-XRF system using the D09B X-ray fluorescence beam line at the Brazilian Synchrotron Light Source (LNLS, Campinas, São Paulo State) was employed for this purpose. The data were analyzed using a chemometric tool called soft independent modelling of class analogy (SIMCA). The promising results from SIMCA models reinforce the evidence that plants infected by citrus greening (both asymptomatic and symptomatic) undergo alterations in their micro- and macronutrient compositions.